O PROCESSO DE ENSINO-APRENDIZAGEM EM SALA MULTISSERIADA: SÍMBOLO DE LUTA E RESISTÊNCIA PARA A EDUCAÇÃO DO CAMPO - Jesus, Irani da Silva de (2020)
This study seeks to investigate the teaching-learning process in a multi-graded classroom of a rural school in the city of Linhares / ES and to envision paths for a humanizing pedagogical performance. It is justified by the relevance it represents for the